KNOWLEDGE MANAGEMENT FOR LEARNING MANAGEMENT SYSTEM MENGGUNAKAN BALANCE SCORECARD DAN CRITICAL SUCCESS FACTOR - Reko Syarif Hidayatullah; Dewi Mustari (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2020)
Technology that is increasingly developing will create a life journey to the digital world. Currently, information technology is very helpful in daily work from the lower class to the top. They can use information technology to get the information needed. Currently X University is developing a distance learning process using the Learning Management system information system as a result of the outbreak that is currently hitting this country, of course, lectures are currently being stopped. And learning is done by oline. Of course, currently online learning can be done using a variety of existing applications, but it certainly has shortcomings in data management when using common applications. Therefore university x developed an online learning system using a Learning Management System (LMS) to make it easier for university x to monitor online learning activities. So that everything can be realized properly, an assessment strategy is made based on existing problems by getting solutions from SWOT analysis, Balanced Scorecard and also Critical Success factors to assess what needs are needed so that the use of LMS can be successful by using Knowledge Management.